Analisis Dampak Pembelajaran Penugasan Berbasis Web Pada Mahasiswa Pendidikan Matematika Universitas Bengkulu - Syafdi Maizora; Dadang Juandi (UNIB Press, 2022)
Abstract This study aims to see the impact on mathematics education students at Bengkulu University learning web-based assignments assisted by GeoGebra. This research is a qualitative descriptive study. The subjects of this study were 36 students in the second-semester class of 2020 at the Mathematics Education Study Program at Bengkulu University. The research instruments were interviews, questionnaires, and track record documents on the web. The study's results stated that student self-study could be motivated by assignments with structured material delivered through the learning web and embedded with the GeoGebra application for geometry material. Each student's independent study duration varies, with an average study time of 140 minutes. The most independent study time is done at night because students feel comfortable. In line with their mastery of the material due to independent learning, all students have high confidence in presenting learning outcomes in front of the class. All students like GeoGebra-assisted web-based learning. Thirty-three students, or 92%, agreed to apply this learning to further learning. Students ask the lecturer to pay attention to the completion time of the assignment based on the material's content, and the lecturer makes an agreement with them. Keywords: assignment learning, GeoGebra, web-based learning